Analisis Efektivitas Proses Rekrutmen Online Pada Karyawan Divisi Human Resource Departemen Pt Fabindo Sejahtera Tangerang - Indah Cahyaningrum; Nurul Ilham (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
- This study aims to analyze the effectiveness of the online recruitment process for employees in PT Fabindo Sejahtera Tangerang, identify how the company obtains candidates who meet the required qualifications, and examine the challenges that arise during the online recruitment process. This research employs a qualitative descriptive method through interviews, observations, and documentation involving five informants from the Human Resource Department. The results show that online recruitment accelerates the hiring process and expands the applicant pool; however, it has not been fully effective due to the high number of applicants who do not meet the required qualifications, the high cost of platform subscriptions, and limitations in assessing candidates’ character and commitment virtually. To address these issues, the human resource departemen of PT Fabindo Sejahtera conducts more thorough manual selection, utilizes behavioral observations during online interviews, and continuously evaluates the recruitment platforms used. The challenges encountered include low applicant relevance, difficulties in assessing non-technical characteristics, technical obstacles, and a lack of candidate commitment. System evaluation and improved recruitment strategies are required to enhance process effectiveness in the future.